Effect of Lower Limb Alignment in Medial Meniscus–Deficient Knees on Tibiofemoral Contact Pressure. Issue 2 (30th January 2019) - Willinger, Lukas; Foehr, Peter; Achtnich, Andrea; Forkel, Philipp; Voss, Andreas; Liska, Franz; Lacheta, Lucca; Imhoff, Andreas B.; Burgkart, Rainer
Background: Degenerative medial meniscal tears and subsequent partial meniscal resection compromise meniscal function and lead to an overload of the medial compartment. In addition, lower limb alignment plays a key role in load distribution between the medial and lateral knee compartments, and varus alignment is a potential risk factor for medial osteoarthritis. Purpose/Hypothesis: The purpose of this biomechanical study was to investigate the effect of valgus and varus alignment on peak pressure and contact area in knees with concomitant horizontal medial meniscal tears and subsequent leaflet resection. It was hypothesized that varus alignment in combination with meniscal loss leads to the highest peak pressure within the medial compartment. Study Design: Controlled laboratory study. Methods: Six fresh-frozen human cadaveric knees were axially loaded using a 1000-N compressive load in full extension with the mechanical axis rotated to intersect the tibial plateau at 40%, 45%, 50%, 55%, and 60% of its width (TPW) to simulate varus and valgus alignment. Tibiofemoral peak contact pressure and contact area of the medial and lateral compartments were determined using pressure-sensitive foils in each of 4 different meniscal conditions: intact, 15-mm horizontal tear of the posterior horn, inferior leaflet resection, and resection of both leaflets. Results: The effect of alignment on peak pressure (normalized to the neutral axis) within the medial compartment in cases of an intact meniscus was measured as follows: varus shift resulted in a mean increase in peak pressure of 18.5% at 45% of the TPW and 37.4% at 40% of the TPW, whereas valgus shift led to a mean decrease in peak pressure of 8.7% at 55% of the TPW and 23.1% at 60% of the TPW. Peak pressure changes between the intact meniscus and resection within the medial compartment was less in valgus-aligned knees (0.21 MPa at 60% TPW, 0.59 MPa at 50% TPW, and 0.76 MPa at 40% TPW). Contact area was significantly reduced after partial meniscal resection in the neutral axis (intact, 553.5 ± 87.6 mm 2 ; resection of both leaflets, 323.3 ± 84.2 mm 2 ; P < .001). This finding was consistent in any alignment. Conclusion: Both partial medial meniscal resection and varus alignment led to an increase in medial compartment peak pressure. Valgus alignment prevented medial overloading by decreasing contact pressure even after partial meniscal resection. A horizontal meniscal tear did not influence peak pressure and contact area even in varus alignment. Clinical Relevance: As a clinical consequence, partial meniscal resection should be avoided to maintain the original biomechanical behavior, and the mechanical axis should be taken into account if partial meniscectomy is necessary.